THE ISLAMIC RELIGIOUS EDUCATION TEACHERS' STRATEGIES IN FORMING STUDENT CHARACTER AT MAARIF NU NASHIRUL HUDA JUNIOR HIGH SCHOOL - Hilmi, Muhammad Pahrudin (ASWAJA: Jurnal Pendidikan dan Keislaman, 2025)
Character education plays a crucial role in shaping moral individuals and communities. Islamic Religious Education (PAI) teachers at Maarif NU Nashirul Huda Middle School bear a significant responsibility in preparing a generation grounded in faith and piety, especially amidst the nation's moral crisis. This study aims to: (1) describe the strategies of Islamic Religious Education (PAI) teachers in shaping students' character, (2) identify supporting and inhibiting factors, and (3) find solutions to the obstacles encountered. The method used was field research with a qualitative approach, utilizing observation, interviews, and documentation. Data analysis was conducted using triangulation to ensure validity. The results show that Islamic Religious Education (PAI) teachers use learning strategies such as cooperative learning, Problem-Based Learning (PBL), and Project-Based Learning (PjBL) by integrating character values. Religious activities such as congregational prayer, BDI extracurricular activities, the culture of salim (shalim), Pondok Ramadhan (Ramadan Islamic Boarding School), istighotsah (Islamic charity), infaq (charity), and PHBI (Islamic Religious Behavior). To overcome these obstacles, Islamic Religious Education (PAI) teachers incorporate Quranic verses and Hadith into each lesson as an effective solution